2019
DOI: 10.1016/j.amsu.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Primary infected hydatid cyst of the thigh in a young lady; case report with literature review

Abstract: Hydatid disease present in certain parts of the world. Infection of the musculoskeletal system occur in less than 0.5%.A 24-year-old lady had a painful mass in the inner aspect of the right thigh. MRI of the thigh showed a mixed signal intensity lesion measured about 65*100 mm, the mass was related to the muscle and the superficial femoral artery and its cavity had multiple septations.During surgery an infected hydatid cyst of the muscle was found, evacuation was done with removal of the cyst. The patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…Hydatid cysts occur in the lungs and liver or other sites of body but primary CE in the muscle of thigh is rare and reported in the literature [ 2 ], [ 3 ], [ 5 ], [ 17 ]. Because of their rich vascular supply, neck muscles are the other muscular part of the body in which hydatid cysts have been found [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydatid cysts occur in the lungs and liver or other sites of body but primary CE in the muscle of thigh is rare and reported in the literature [ 2 ], [ 3 ], [ 5 ], [ 17 ]. Because of their rich vascular supply, neck muscles are the other muscular part of the body in which hydatid cysts have been found [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case report by Tahir et al [ 17 ], the patient had a painful mass on the inner aspect of right thigh. The MRI findings showed that the mass was related to the superficial femoral artery and the muscle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations